(untitled) (Veterinary Science, 2025)
Ixodes affinis is a tick that belongs to a group that includes four species which are distributed from northern Argentina to Canada. A single species, Ixodes keieransi, has been reported in six states of Mexico republic, feeding on mammals and birds, mainly of wild habits. This species of tick has been incriminated as a potential vector of Borreli burgdorferi, the etiological agent of Lyme disease, between wild and domestic animals. Despite being reported mainly in wild animals; it can parasitize domestic animals such as dogs when they are taken to the jungle or forests for hunting or recreational activities. This document shows the morphological description of the tick, hosts, life cycle, ecology, distribution, and adaptation of this wild species into rural areas of Mexico.